2021
DOI: 10.7554/elife.65309
|View full text |Cite
|
Sign up to set email alerts
|

The generation of cortical novelty responses through inhibitory plasticity

Abstract: Animals depend on fast and reliable detection of novel stimuli in their environment. Neurons in multiple sensory areas respond more strongly to novel in comparison to familiar stimuli. Yet, it remains unclear which circuit, cellular, and synaptic mechanisms underlie those responses. Here, we show that spike-timing-dependent plasticity of inhibitory-to-excitatory synapses generates novelty responses in a recurrent spiking network model. Inhibitory plasticity increases the inhibition onto excitatory neurons tune… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 117 publications
4
51
1
Order By: Relevance
“…Therefore, we extend previously studied roles of inhibitory plasticity, which include the stabilization of excitatory rates (Vogels et al, 2011;Sprekeler, 2017), decorrelation of neuronal responses (Duarte and Morrison, 2014), preventing winner-take-all mechanisms in networks with multiple stable states (Litwin-Kumar and Doiron, 2014) or generating differences among novel versus familiar stimuli (Schulz et al, 2021). Recent computational studies also include novel ways of inhibitory influence, like presynaptic inhibition via GABA spillover (Naumann and Sprekeler, 2020) or an input-dependent inhibitory plasticity mechanism (Kaleb et al, 2021).…”
Section: Predictionsmentioning
confidence: 72%
“…Therefore, we extend previously studied roles of inhibitory plasticity, which include the stabilization of excitatory rates (Vogels et al, 2011;Sprekeler, 2017), decorrelation of neuronal responses (Duarte and Morrison, 2014), preventing winner-take-all mechanisms in networks with multiple stable states (Litwin-Kumar and Doiron, 2014) or generating differences among novel versus familiar stimuli (Schulz et al, 2021). Recent computational studies also include novel ways of inhibitory influence, like presynaptic inhibition via GABA spillover (Naumann and Sprekeler, 2020) or an input-dependent inhibitory plasticity mechanism (Kaleb et al, 2021).…”
Section: Predictionsmentioning
confidence: 72%
“…For unpredicted stimuli, this feedback is not effective, resulting in non-sparse firing indicating a mismatch. In [ 60 ], a similar mechanism is employed to generate mismatch signals for novel stimuli. In this study, the strength of the inhibitory feedback needs to be learned by means of inhibitory synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, the WTA mechanism is controlled by the predictions (dAPs) and implemented by static inhibitory connections. Furthermore, the model in [ 60 ] can learn a set of elements, but not the order of these elements in the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Many related studies have shown evidence for cortical novelty responses across brain regions, with wide variation in the effort to control for adaptation ( Kato et al, 2015 ; Makino and Komiyama, 2015 ; Garrett et al, 2020 ; Poort et al, 2021 ; Schulz et al, 2021 ; Homann et al, 2022 ; Montgomery et al, 2022 ). In most cases, consistent with efficient coding, novel stimuli evoke more spiking activity than familiar.…”
Section: Efficient Coding In Primary Visual Cortexmentioning
confidence: 99%